SUMBER DALIL MANAJEMEN KEUANGAN SYARIAH: (Kajian Prinsip dan Kontrak Manajemen Keuangan Syariah Dalam Dalil Al-Quran dan Sunnah) - Pratanto Rahayu, Wedi (Irtifaq, 2025)
This study examines the Qur’anic and Prophetic evidences (dalil) in a clearer, adaptive, and applicative manner concerning the principles and contracts of Islamic financial management. The study is motivated by the growing need for financial management concepts that are not only technically effective but also aligned with ethical and religious values, grounded in the definitive sources (al-Qur’an and Sunnah) in a more explicit, adaptive, and applicative framework. Principally, Islamic financial management applies foundational principles such as the prohibition of riba (usury), prohibition of maysir (speculative behavior), obligation to fulfill contracts, the principle of money as a medium of exchange, risk-sharing, compliance with Sharia rules, and the command to uphold justice. In practice, Islamic financial management employs various contracts, both tabarru’ contracts (benevolent contracts) such as hibah, wakalah, kafalah, hawalah, rahn, qard, and wadi‘ah, as well as tijari contracts (commercial-oriented contracts) such as murabahah, mudharabah, ijarah, musyarakah, and sharf. The findings indicate that the principles and contracts of Islamic financial management are explicitly established and legitimized in the Qur’an and Sunnah, as supported by Qur’anic exegesis from classical scholars and hadith commentaries. Keywords:, al-Qur’an, Sunnah, Finac management of syariah, contract principles